Immune Checkpoint Blockade – How Does It Work in Brain Metastases? - Lorger, Mihaela; Andreou, Tereza; Fife, Christopher; James, Fiona (Frontiers in Molecular Neuroscience, 2019)
Immune checkpoints restrain the immune system following its activation and their inhibition unleashes anti-tumor immune responses. Immune checkpoint inhibitors revolutionized the treatment of several cancer types, including melanoma, and immune checkpoint blockade with anti-PD-1 and anti-CTLA-4 antibodies is becoming a frontline therapy in metastatic melanoma. Notably, up to 60% of metastatic melanoma patients develop metastases in the brain. Brain metastases are also very common in patients with lung and breast cancer, and occur in 20-40% of patients across different cancer types. Metastases in the brain are associated with poor prognosis due to the lack of efficient therapies. In the past, patients with brain metastases used to be excluded from immune-based clinical trials due to the assumption that such therapies may not work in the context of “immune-specialized” environment in the brain, or may cause harm. However, recent trials in patients with brain metastases demonstrated safety and intracranial activity of anti-PD-1 and anti-CTLA-4 therapy. We here discuss how immune checkpoint therapy works in brain metastases, with focus on T cells and the cross-talk between brain metastases, the immune system, and tumors growing outside the brain. We discuss major open questions in our understanding of what is required for an effective immune checkpoint inhibitor therapy in brain metastases.